Information communication technology standardization for e-business sectors : integrating supply and demand factors - Jakobs, Kai, 1957- (Hershey : Information Science Reference, 2009)
'This book studies the nature, relevance, and quality of standards with ICTs and the impact they have on businesses'--Provided by publisher
'Advances in IT standards and standardization research (AISSR) series ..., ISBN [i.e. ISSN] 1935-3391'--P. facing t.p. verso.
'Premier reference source'--Cover.
Includes bibliographical references (p. 270-285) and index
Keywords: Information technology -- Standards; Electronic commerce -- Information technology